The Secret War : Spies, Ciphers, and Guerrillas 1939-1945 - Hastings, Max (New York Harper, An Imprint of HarperCollinsPublishers, 2016)
An examination of one of the most important yet underexplored aspects of World War II--intelligence--shows how espionage successes and failures by the United States, Britain, Russia, Germany, and Japan influenced the course of the war and its final outcome.
Include Illustrations and Ijndex
Keywords: Secret service -- Underground movements, War -- Cryptography -- Electronic intelligence -- Espionage